Factors Affecting Farmers’ Perception toward Agricultural Land Sustainability in Peri-Urban Areas of Pekalongan City - Imade Yoga Prasada; Masyhuri Masyhuri (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Over the past few decades, agricultural land sustainability on the peri-urban areas face a threat to the agricultural land conversion, especially on the peri-urban areas of Pekalongan City. The sustainability of agricultural land is determined by the level of farmers’ perception. Therefore, this research was conducted to determine the factors that influence farmers’ perceptions toward agricultural land sustainability in peri-urban areas of Pekalongan City. The peri-urban areas of Pekalongan City were selected by purposive sampling method with a total sample of 90 farm owners and cultivators. Data were analyzed using OLS (Ordinary Least Square) regression model. The results have shown that the factors influencing farmers’ perceptions toward agricultural land sustainability in the peri-urban area of Pekalongan City were farmers’ knowledge, farmers’ land tenure and access to information. Based on the results of the study, the variables of farmers’ knowledge and land tenure had a negative impact, while the access to agricultural information had a positive impact on farmers’ perceptions. These results have the implication for farmers, that their perceptions can be improved by making advances to the quality of agricultural land in the suburbs, reducing both production and price risks and increasing the intensity of counseling or training related to agricultural activities in the suburbs of Pekalongan City.